1997
DOI: 10.1046/j.1469-8137.1997.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium deficiency on cell water relations and elongation of tap and lateral roots of maritime pine seedlings

Abstract: SUMMARYThe effects of potassium deficiency (KD) and all-macronutrient deficiency (MD) on elongation of tap and lateral roots were studied on maritime pine seedlings (Pinus pinaster Ait.) in hydroponic culture.Tap root elongation was unaffected by either of the two deficiencies. By marked contrast, lateral root elongation was strongly reduced. The analyses of cell turgor pressure and relative elemental growth rate (REGR) profile in the growing zone allowed us to determine the effects of the nutrient stresses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…However, most investigators concluded that the hydraulic conductance was suciently high and that, instead, control of wall properties was responsible for treatment-associated dierences in the expansion of leaf and root cells (e.g. Cosgrove et al 1984;Tomos and Pritchard 1994;Triboulot et al 1997). The latter conclusion has its origin in the work of Green et al (1971) on Nitella and Lockhart's (1965) empirical growth model, which relates RGR to the extensibility properties (m) and the yield threshold (Y) of the cell wall:…”
Section: Introductionmentioning
confidence: 98%
“…However, most investigators concluded that the hydraulic conductance was suciently high and that, instead, control of wall properties was responsible for treatment-associated dierences in the expansion of leaf and root cells (e.g. Cosgrove et al 1984;Tomos and Pritchard 1994;Triboulot et al 1997). The latter conclusion has its origin in the work of Green et al (1971) on Nitella and Lockhart's (1965) empirical growth model, which relates RGR to the extensibility properties (m) and the yield threshold (Y) of the cell wall:…”
Section: Introductionmentioning
confidence: 98%
“…Such an increase in P is not the norm in plant tissues. In roots, P is usually 0.5 MPa in the growth zone, but it remains constant or decreases slightly as cells move away from the growth zone (Frensch & Hsiao, 1993 ;Pritchard, 1994 ;Triboulot et al, 1997). It would be interesting to assess whether this higher turgor in mature leaves compared with mature roots could depend on the structural requirements for self support in mature leaves.…”
Section: mentioning
confidence: 99%
“…Although the beneficial effect of increased K ϩ supply on wall extensibility has been demonstrated (Métraux and Taiz, 1977), the presence of K ϩ salts in the nutrient solution can inhibit root-cell elongation by reducing cell wall plasticity in the root-expansion zone (Pritchard et al, 1987). The effect of K ϩ on root elongation seems to be species specific (Pritchard, 1994), cultivar specific (Hackett, 1968), and root-type specific (Hackett, 1968;Triboulot et al, 1997).…”
mentioning
confidence: 99%